Human Aspects of IT for the Aged Population. Technology and Society c - Gao, Qin.; Zhou, Jia.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This three volume set of LNCS 12207, 12208 and 12209 constitutes the refereed proceedings of the 6th International Conference on Human Aspects of IT for the Aged Population, ITAP 2020, held as part of the 22nd International Conference, HCI International 2020, which took place in Copenhagen, Denmark, in July 2020. The conference was held virtually due to the COVID-19 pandemic. The total of 1439 papers and 238 posters have been accepted for publication in the HCII 2020 proceedings from a total of 6326 submissions. ITAP 2020 includes a total of 104 regular papers which are organized in topical sections named: Involving Older Adults in HCI Methodology , User Experience and Aging, Aging and Mobile and Wearable Devices, Health and Rehabilitation Technologies, Well-being, Persuasion, Health Education and Cognitive Support, Aging in Place, Cultural and Entertainment Experiences for Older Adults, Aging and Social Media, Technology Acceptance and Societal Impact.
Aging and Social MediaMapping Intergenerational Masculinities on Instagram -- Ageism and Media Generations in the Croatian Post-socialist Context.-"You Don t Need Instagram, it s for Young People: Intergenerational Relationships and ICTs Learning Among Older Adults.-Young and Elderly Fashion Influencers.-Methods Matter: Assessment of the Characteristics of a Sample to Analyze Digital Practices and Social Connectedness in Later Life.-Consuming Fake News: A Matter of Age? The Perception of Political Fake News Stories in Facebook Ads.-Masculinities and Ageing: Deconstructing Online Representations among Portuguese Speaking Users -- Intergenerational social media use: expectations of adults and elder users. Addressing Fear and Lack of Knowledge of Older Adults Regarding Social Network Sites -- The Effect of Social Media Use on Older Adults' Loneliness-The Moderating Role of Self-Disclosure.-How to Beautify the Elderly?: A Study on the Facial Preference of Senior Citizens -- Technology Acceptance and Societal Impact -- Technologies and Images of Older Women.-Digital Inclusion or Digital Divide for Older Immigrants? A Scoping Review -- Expectations and Sensemaking: Older People and Care Robots.-The Impact of the Relationship and Family Status in Retirement Age on Women s Incorporation of Technical Devices in their Everyday Life.-Understanding the Influence of AI Voice Technology on Visually Impaired Elders Psychological Well-Being: an Affordance Perspective.-A Study on Technology Anxiety Among Different Ages and Genders.-To Do or Not to Do: How Socio-Demographic Characteristics of Older Adults are Associated with Online Activities.-Understanding the Exclusion Issues of Mobility-as-a-Service (MaaS): the Potential Problems of Older Travellers Involvement -- Intergenerational Communication in Traditional and Virtual Bulgarian Families -- The Relationship between Social Participation and Internet Addiction in Older Persons.-Age and the City: The Case of Smart Mobility.-The Effects of Increasing Degree of Unreliable Automation on Older Adults' Performance.-Older People as Digital Newcomers: From Evidence to Intervention Proposal.-Understanding Older Adults Vulnerability and Reactions to Telecommunication Fraud: The Effects of Personality and Cognition -- Internet Use and Loneliness among Older Adults: The Moderating Role of Self-Perceptions of Ageing.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Data structures (Computer science).; Information theory; Social sciences -- Data processing; Computer engineering; 9; Electronic commerce; User Interfaces and Human Computer Interaction; Data Structures and Information Theory; Computer Application in Social and Behavioral Sciences; Computer Engineering and Networks; e-Commerce and e-Business.